FEATURES OF COLOR LASER MARKING ON METALS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the research carried out at the Rezekne Academy of Technology, the technology for color laser marking on chromium-nickel base and other metal bases was used in industrial production from the point of view of the repeatability and stability of the produced color markings. The study and research was done during the Erasmus internship by the authors at the Academy of Technology in Rezekne, Latvia. For this purpose, an AISI 304 color palette consisting of fifteen colors was developed and implemented. After the practical experiments, the dependence of the obtained colors on the various parameters of the laser processing was analyzed. The resulting colors were then tested using optical, scanning electron and atomic force microscopy, and the configuration of the oxide films was determined by Raman spectroscopy. The resulting colors are of appropriate uniformity, brightness and cover almost all spectral zones, and the resulting colors are of many times better quality than other metallic bases. A color standardization and palette repeatability test was also performed by evaluating the reflectance spectra of the formed colors. The color palette demonstrated high repeatability for all but one particular color. In parallel, the stability of the color markings was studied in terms of environmental, mechanical and chemical resistance. The resulting colors show high resistance to most environmental conditions; however, exposure to very high temperatures and extreme humidity (100 °C, 90%) and to low temperatures and extreme humidity (-40 °C, 90%) results in degradation of several colors. Colored brands show high hardness and excellent mechanical resistance to external influences and exceptional resistance to various chemicals, except for acid solutions and salts.